Gameplay limiters in free-to-play mobile games - Kangas, Karri (My University, 2020)
As free-to-play mobile games have become the mainstream of mobile games, new monetization methods have also started to emerge. Free-to-play games do not have the direct money flow from purchases or subscriptions like buy-to-play or pay-to-play models do. One way to add monetization into free-to-play games, is to integrate it directly into the core of a game. One of these integrated methods are gameplay limiters. Gameplay limiters are elements which are added to limit playing of the game. This limiting can have many reasons behind it, such as keeping the game interesting for a longer period of time, but the most prevalent reason for limiting is monetization. Some of the most common ways to implement limiters are energy mechanic, life mechanic and time gates. In energy mechanic, whenever the player plays the game, they exhaust an energy resource which gradually regenerates. When player is out of energy, they might be limited out of parts of the game or they might be unable to play the game at all. In life mechanic, whenever the player fails a level (e.g. dies or runs out of time) they lose a life. Hence, successful play is not limited by life mechanic at all but after a few failures, the player might have to wait a long time for their lives to replenish. In time gates, whenever the player does a certain action, (e.g. opens a chest or starts constructing a building) a timer starts. The player then has to wait for the timer to expire before the action is complete. The monetization in these limiters comes from getting over them. Most of gameplay limiters in free-to-play games can be bypassed by money. This brings up issues like limiting PvP (player versus player) games as the players who use money get the advantage of skipping all limiters.

Ilmaismobiilipelien muututtua mobiilipelien valtavirraksi on syntynyt tarve uusille monetisaatio menetelmille. Ilmaispeleillä ei ole samankaltaisia suoria tulonlähteitä kuin peleillä jotka ostetaan tai peleillä joiden pelaamisesta maksetaan esimerkiksi kuukausimaksua. Yksi tapa monetisoida ilmaispelejä on kehittää nämä monetisaatiomenetelmät keskenäiseksi osaksi pelimekaniikkaa. Yksi tällainen menetelmä ovat pelirajoitteet. Pelirajoitteet ovat elementtejä jotka asetetaan peliin rajoittamaan koko pelin tai joidenkin pelin osien pelaamista. Näiden rajoitteiden takana voi olla monia syitä, kuten yritys säilyttää pelaajien kiinnostus peliä kohtaan pidempään, mutta ilmeisin näistä syistä on monetisaatio. Yleisimpiä pelirajoitteita ovat energiamekaniikka, emämämekaniikka ja aikaportit. Energiamekaniikkassa, kun pelaaja pelaa peliä, hän jatkuvasti kuluttaa energiaa. Energiaa palautuu koko ajan, mutta jos energiamäärä menee liian pieneksi, pelin, tai ainakin sen osien, pelaaminen saattaa estyä. Elämämekaniikkassa, kun pelaaja epäonnistuu (esm. kuolee tai häneltä loppuu aika), hän menettää elämän. Tämä rajoite ei rankaise onnistuneesta pelaamisesta, mutta epäonnistumisten jälkeen pelaajaa estetään pelaamasta peliä. Aikaportiteissa, kun pelaaja tekee jonkun toiminnon, (esim avaa arkun tai aloittaa rakennuksen rakentamisen) alkaa ajastin. Pelaajan on odotettava ajastimen loppumista ennen kuin tehty toiminto suorittuu. Pelirajoitteiden monetisaatio syntyy siitä, miten niiden ohi päästään. Suurin osa rajoitteista on mahdollista ohittaa rahalla. Tämä luo ongelmia, kuten miten toisia pelaajia vastaan pelatuissa peleissä, maksavien pelaajien on mahdollista päästä aikarajoitteiden ohi. Tämä antaa siis maksaville pelaajille selvästi etua.
Keywords: Free-to-play, mobile games, limiters, gameplay limiters, time gates, energy mechanics